University governance challenges and opportunities in light of the Fourth Industrial Revolution - Algazo, Fatima Ali; Aldahabi, Zain Mohammed; Alanazi, Amal Marshed; Hajjaj, Rula Yousef (Journal of Economic, Administrative and Legal Sciences, 2025)
This study examines the benefits and problems of the Fourth Industrial Revolution (4IR) for university governance. The statement underscores the need for academic institutions to reconsider and revamp their governing frameworks to accommodate swift progress in technology and digital transformation. The study demonstrates how governance principles such as transparency, engagement, justice, accountability, adaptability, efficiency, sustainability, and inclusivity can assist academic institutions in overcoming 4IR’s obstacles and grabbing hold of benefits such as better information availability, streamlined administrative processes, optimized resource allocation, enhanced learning experiences, and increased performance. From a methodological standpoint, this study analyzes how universities might implement transformative policies to guarantee effective governance in the digital era using a conceptual framework. Significant findings indicate that universities must successfully integrate new technologies, improve decision-making, build collaborations, foster an innovative-driven culture, enhance responsiveness to emerging challenges, and promote interdisciplinary research initiatives to attain competitive advantages in a world that is changing quickly. The study recommends implementing digital governance initiatives, strengthening cybersecurity measures, increasing digital literacy, and establishing regulations to ensure ethical AI use in decision-making.